Residual Impact of Concurrent, Resistance, and High-Intensity Interval Training on Fasting Measures of Glucose Metabolism in Women With Insulin Resistance - Alvarez, Cristian; Ciolac, Emmanuel Gomes; Guimarães, Guilherme Veiga; Andrade, David C; Vasquez-Muñoz, Manuel; Monsalves-Álvarez, Matías; Delgado-Floody, Pedro; Alonso-Martínez, Alicia M.; Izquierdo, Mikel (Frontiers in Physiology, 2021)
We sought to assess the residual effects of 12-weeks of concurrent (CT), resistance (RT) or high-intensity interval (HIIT) training on fasting plasma glucose (FPG) and insulin (FI) measures in adult women with insulin resistance. We also aimed to determine the training-induced, post-training residual impact of CT. A total of adult 45 women (age 38.5±9.2 years) were included in the final analysis and were assigned to a control (CG; n = 13, BMI 28.3±3.6 kg/m2), HIIT (n = 14, BMI 28.6±3.6 kg/m2, 3 session/wk), RT (n = 8, BMI 29.4±5.5 kg/m2, 2 session/wk) or CT (n = 10, BMI 29.1±3.0 kg/m2, 3 session/wk) group, with the latter including both HIIT and RT regimens. Training interventions lasted 12 weeks. Main outcomes were FPG and FI measured at pre- and at 24-h and 72-h post-training (FPG24h, FI24h, and FPG72h, FI72h, respectively). Secondary endpoints were body composition/anthropometry and the adiposity markers waist circumference (WC) and tricipital skinfold (TSF). The residual effects 72-h post-training (delta [∆]) were significantly poorer (all P < 0.01) in the CT group (∆FPG72h + 6.6 mg/dL, η2: 0.76) than in the HIIT (∆FPG72h +1.2 mg/dL, η2: 0.07) and RT (∆FPG72h +1.0 mg/dL, η2: 0.05) groups. These findings reveal that HIIT reduces FPG and RT reduces FI 24-h post-training; and both exercise interventions alone have remarkably better residual effects on FPG and FI (post 72-h) than CT in women with insulin resistance.